Making work fun : investigating antecedents of perceived enjoyment in human computation games for information sharing - Pe-Than, Ei Pa Pa (2014)
The advent of online games, crowdsourcing, and user-generated content has led to the emergence of a new paradigm called the Human Computation Game (HCG) which utilizes games as a motivator to encourage users’ participation in human computation. HCGs are different from games for pure entertainment which emphasize play and fun, rather than output generation. Therefore, research has yet to fully explore the factors underlying players’ perception of HCG enjoyment. In this paper, we study the influence of motivational needs satisfaction and perceived output quality on perceived HCG enjoyment using a survey (N = 205) of a location-based information sharing HCG called SPLASH, developed as part of our research. According to the results, perceived needs for autonomy, competence, and relatedness influence perceived enjoyment of HCGs, suggesting that HCGs that fulfill these three needs are more likely to be enjoyable, thereby encouraging players to make useful computations. The results also show that participants who perceive higher levels output relevancy report a greater level of enjoyment, indicating that HCGs that assist players in generating relevant outputs are more likely to be perceived as enjoyable.